2021
DOI: 10.1021/acsami.1c11628
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation Strategies for Highly Stable Perovskite Solar Cells under Severe Stress Testing: Damp Heat, Freezing, and Outdoor Illumination Conditions

Abstract: A key direction toward managing extrinsic instabilities in perovskite solar cells (PSCs) is encapsulation. Thus, a suitable sealing layer is required for an efficient device encapsulation, preventing moisture and oxygen ingression into the perovskite layer. In this work, a solution-based, low-cost, and commercially available bilayer structure of poly(methyl methacrylate)/styrene-butadiene (PMMA/SB) is investigated for PSCs encapsulation. Encapsulated devices retained 80% of the initial power conversion efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 69 publications
0
43
0
Order By: Relevance
“…However, a possible concern in polymer encapsulation is the solvent used for polymer coating, since it has been reported that poly­(methyl methacrylate) (PMMA) deposition from chlorobenzene solutions can result in damage to the 2,2’,7,7’-tetrakis­[ N , N -di­(4-methoxyphenyl)­amino]-9,9’-spirobifluorene (spiroOMeTAD) layer . Various polymers have been reported for the encapsulation of perovskite films and devices, such as PDMS, plasma polymer film from adamantane precursor, poly­(methylmethacrylate) (PMMA), , parylene C, TPU, PMMA/vulcanized silicone rubber, PMMA//styrene-butadiene (SB), fluoropolymer coating, etc. In addition to polymer films, roll-transferred graphene has also been used as well as spray-coated reduced graphene oxide (rGO) .…”
Section: Encapsulation Methods and Materials For Pscsmentioning
confidence: 99%
“…However, a possible concern in polymer encapsulation is the solvent used for polymer coating, since it has been reported that poly­(methyl methacrylate) (PMMA) deposition from chlorobenzene solutions can result in damage to the 2,2’,7,7’-tetrakis­[ N , N -di­(4-methoxyphenyl)­amino]-9,9’-spirobifluorene (spiroOMeTAD) layer . Various polymers have been reported for the encapsulation of perovskite films and devices, such as PDMS, plasma polymer film from adamantane precursor, poly­(methylmethacrylate) (PMMA), , parylene C, TPU, PMMA/vulcanized silicone rubber, PMMA//styrene-butadiene (SB), fluoropolymer coating, etc. In addition to polymer films, roll-transferred graphene has also been used as well as spray-coated reduced graphene oxide (rGO) .…”
Section: Encapsulation Methods and Materials For Pscsmentioning
confidence: 99%
“…5a). Therefore, similar to Pb-based perovskites, [101][102][103] fully understanding the degradation mechanism is reasonably necessary to solve the stability issue in this type of perovskites. Generally, as discussed, the facile oxidation of Sn 2+ to Sn 4+ was identied as the main instability reason of these materials, which leads to deteriorating the thin lm morphology and optoelectronic properties, as well as high-density p-type doping.…”
Section: Chemical Stability and Degradation Mechanismmentioning
confidence: 99%
“…Inspired by the DSSCs sandwich device structure, the two TCO electrodes can be used as front and back electrodes to fabricate the PSC with self-encapsulation features to protect the devices from moisture and improve the device stability. 56,[107][108][109] Using this architecture, Heo et al fabricated semi-transparent planar sandwich PSCs with almost a hysteresis-free PCE of 15.8% and over 20 days of stability (5% dropped PCE) without any extra encapsulation. 56 They used semi-transparent FTO glass/TiO 2 /MAPbI 3 /HTL and ITO/PEDOT:PSS as the first and second stack, respectively.…”
Section: Pedot:pss For Pscsmentioning
confidence: 99%